Association between body mass index and operative morbidity in women undergoing hysterectomy for benign indications: a cohort study - Kose, Varsha; Kawthalkar, Anjali; Bhalerao, Anuja; Nayse, Jaydeep; Jain, Sheela; Kose, Saurabh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hysterectomy is the most common gynaecological operation performed in the world. This study was done to investigate association between body mass index (BMI) and operative morbidity in women who underwent hysterectomy for benign indications. Methods: Total 201 women were studied. 114 (56.7%) had BMI between 20-24.9 and 87 (43.3%) had BMI 25 and above. In both groups, abdominal and vaginal hysterectomy were performed. They were compared for duration of surgery, intraoperative blood loss, postoperative fever, wound infection, secondary haemorrhage, deep vein thrombosis, resuturing and readmission. Results: Mean duration of surgery in women with BMI 20-24.9 was 2.47 hours, standard deviation was 0.665 and in women with BMI 25 and above was 2.45 hours, and standard deviation was 0.589. T value was 0.215 and p value was 0.83 which is not statistically significant. Mean blood loss during surgery with BMI less than 25 was 184.74 ml, standard deviation was 104.518 and with BMI more than 25 was 200.57 ml, and standard deviation was 77.462. T value was 1.234 and p value was 0.219 which is not clinically significant. Out of 114 women with BMI less than 25, 16 (38.1%) had complications and 98 (61.6%) had no complications. Out of 87 women with BMI more than 25, 26 (61.9%) had complications and 61 (38.4%) had no complications, Chi square test was 7.48, and p value of 0.006 which was clinically significant. It shows that women with BMI 25 and above had more chances of postoperative complications. Conclusions: There is no statistically significant difference in intraoperative blood loss and duration of surgery in both women with normal BMI and women with BMI 25 and above who underwent hysterectomy. But postoperative complications in terms of wound infection, fever, bleeding, necessity of resuturing and readmission were more in women with BMI 25 and above as compared to women with normal BMI.